Resource management mechanism of a commercial bank - E. A. Posnaya; E. Yu. Cherkashina; N. V. Yurchenko; O. I. Ditsulenko (Вестник Северо-Кавказского федерального университета)
Introduction. The main function of commercial banks in the economy is to help mobilize the savings of the population, directing them to the most effective use that increases the total amount of investment and the potential for economic growth. Thus, banks are one of the main structures for ensuring financial stabilization in the state and creating conditions for supporting macroeconomic growth.Goal. The study aims to propose an optimal mechanism for managing the resources of a commercial bank.Materials and methods. Objectively, necessary conditions for creating an effective banking system are the possibility and practical implementation of the transfer of financial resources between business entities, providing service consumers with freedom of choice between various objects for placing temporarily free funds, as well as providing the same (equal) rights to everyone who creates demand for financial resources, the presence of a developed banking system. The use of coefficient, graphic, comparative and other methods of financial analysis allow the authors to most qualitatively formulate proposals regarding increasing the efficiency of resource management of a commercial bank.Results and discussion. The development of the financial system leads to increased competition between commercial banks for resources and effective areas for their placement. This may lead to a gradual decline in the profitability of banking activities.Conclusion. As a result of the study, a system of the highest quality and effective management of banking resources was developed and proposed.